THYROID HORMONE RESISTANCE SYNDROME (THR): A CASE REPORT - Omar, W Mohd Hilmi bin W.; Ong, Jia Cheng; Hussain, Suhaimi (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION/BACKGROUND Thyroid hormone resistance syndrome (THR) is a rare condition caused by defects in either one of the two thyroid hormone receptors which leads to tissue unresponsiveness to circulating thyroid hormones. The presentations vary depending on which receptor is affected. CASE A 3-year-old female who had a couple of admissions for tonsillitis was incidentally found to have failure to thrive, global developmental delay, intermittent tachycardia, and family history of goitre. She had soft dysmorphism, a baseline heart rate of 80 per min, no obvious goitre, and no skeletal dysplasia. Systemic examinations were unremarkable. Serial thyroid function tests (TFT) showed persistently high thyroid stimulating hormone (TSH) and FT4. TFT samples were sent to different biochemical laboratories and the results were similar. Autoantibody screening such as thyroid receptor antibodies, antithyroglobulin antibodies, and thyroid peroxidase antibodies were all negative. Her liver function, creatine kinase and lipid profile were normal. Thyroid ultrasound showed homogeneous enlargement of both thyroid lobes with increased vascularity within. MRI of the brain and the pituitary gland was normal which ruled out a TSHoma. Both her and her father have mutation R243W in the thyroid hormone beta gene thus confirming the diagnosis of THR-beta. CONCLUSION Diagnosis of THR was challenging in view of its rarity, wide spectrum of presentations, and lack of awareness among physicians.